THE PROBLEM OF COMPONENTIAL ANALYSIS OF MEANING IN PRESENT DAY LEXICOLOGY (Konferensiyalar | Conferences, 2024)
The theme explores challenges in dissecting meaning into components within contemporary lexicology. Delving into the intricacies of compone analysis, the abstract likely addresses evolving linguistic theories and methodologies, shedding light on the complexities inherent in deciphering meaning structures in the lexicon of the present day.